Cyclosporine Therapy for Acquired Factor VIII Inhibitor in a Patient with Systemic Lupus Erythematosus - Schulman, S; Langevitz, P; Livneh, A; Martinowitz, U; Seligsohn, U; Varon, D (Thrombosis and Haemostasis, 1996)
The case of a 27-year-old woman with systemic lupus erythematosus and development of an autoantibody against factor VIII during an exacerbation of her underlying disorder is described. Attempts to eliminate the antibody with high dose gammaglobulin and repeated courses of cyclophosphamide failed, whereafter she received cyclosporine in increasing doses. When therapeutic serum levels of cyclosporine were achieved (150-350 ng/ml) the inhibitor rapidly decreased and disappeared with a concomitant normalization of the factor VIII levels. Treatment with cyclosporine was subsequently reduced and discontinued after one year, and at present no inhibitor is detectable. In view of the successful results with cyclosporine treatment in 4 of 6 previous cases and in all 3 previous cases with autoimmune disorders, this regimen should be evaluated in a systematic manner as a potential first line drug in patients with acquired hemophilia and an underlying autoimmune disorder.